Pemanfaatan E-Learning Pada Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Pipit Putri Hariani; Sri Ngayomi Yudha Wastuti (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2020)
This research is a qualitative descriptive study that examines the use of e-learning in accounting students in the morning 8A accounting study program in the distance learning conditions due to the impact of the co-19 pandemic. Data collection uses data reduction steps, data display and conclusion making using interview techniques through telephone connections and deepening through WhatsApp chat. The results obtained are the level of respondents' understanding of the use of e-learning as a distance learning media as a whole at a rate of 70%, the level of willingness to continue the use of e-learning as a whole is at 25% while the level of need for the presence of lecturers in real is as much as 100%